A two-dimensional AgNb2PS 10 Fabrication of a wide-spectrum polarimetric optical detection device based on materials

CN122977441APending Publication Date: 2026-10-27SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611072984.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,目前报道的二维各向异性材料普遍存在带隙范围有限、光电转换效率偏低的问题,严重限制其在可见光波段的偏振探测应用,难以满足高精度、宽波段探测的实际需求

Benefits of technology

(1)本发明公开了一类二维层状过渡金属硫族材料,同时给出其合成工艺与实际应用方案。以Ag、Nb、P、S作为基础反应物,I2单质充当气相输运助剂,借助化学气相输运工艺,首次合成出大尺寸、结晶品质优异的二维过渡金属硫族化合物 AgNb2PS10。对产物实施机械剥离后可得到少层片材,该少层样品具备优良光电特性,能够应用于发光元件与光电探测装置当中。并首次将所述二维过渡金属硫族化合物 AgNb2PS10应用于偏振宽谱响应光电探测器。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977441A_ABST
    Figure CN122977441A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of two-dimensional semiconductor materials and devices, specifically relating to a two-dimensional AgNb2PS... 10 Fabrication of a broadband polarization optical detector device. This invention involves uniformly mixing elemental silver, niobium, phosphorus, and sulfur, and using elemental iodine as a transport agent to prepare AgNb2PS via chemical vapor deposition. 10 The obtained single-crystal material was mechanically exfoliated to produce layered AgNb2PS. 10 The material is transferred onto a silicon wafer using a dry transfer process, followed by photolithography and gold plating to fabricate optoelectronic polarization devices. This not only overcomes the drawbacks of traditional polarization detectors, such as cumbersome fabrication processes and difficulties in miniaturization and integration, but also addresses the weaknesses in detection performance and photoelectric conversion efficiency of existing two-dimensional anisotropic materials in the visible light band. It simultaneously achieves broad spectral response, high polarization detection accuracy, and a simple fabrication process, providing a novel material approach for developing high-performance, easily integrated polarization photodetectors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional semiconductor materials and devices, specifically relating to a two-dimensional AgNb2PS... 10 Fabrication of broadband polarization light detectors made of materials. Background Technology

[0002] Since the successful exfoliation of graphene, two-dimensional atomic crystal materials have developed rapidly, now encompassing various material systems including metals, semiconductors, and superconductors, greatly enriching the types and application scenarios of low-dimensional functional materials. Among them, two-dimensional transition metal chalcogenides (TMDCs), with their unique layered structure and excellent optoelectronic properties, have become a research hotspot in the field of low-dimensional optoelectronic devices. The atoms within TMDCs are bonded by covalent bonds, while the interlayer structure relies on weak van der Waals forces, making it easy to fabricate atomically thin layers, aligning with the development trend of device miniaturization and lightweighting. Simultaneously, their physical properties exhibit significant size and bonding dependence; when the thickness is reduced to the atomic scale, they will display novel optoelectronic properties distinct from bulk materials, possessing outstanding potential for device applications.

[0003] In the field of photoelectric detection, the spectral response of traditional photoconductive and photovoltaic detectors is strictly limited by the bandgap, resulting in inherent limitations in the detection wavelength. However, photoelectric thermoelectric (PTE) detectors based on the Seebeck effect can overcome this bandgap constraint, offering advantages such as ultra-wide spectral response, low noise, no need for cooling, no need for external power supply, and chopper-free modulation, making them suitable for room-temperature ultra-wideband detection. The PTE effect comprises two stages: photothermal conversion and thermoelectric conversion. After absorbing incident photons, charge carriers transfer energy through electron-electron and electron-phonon interactions, ultimately creating a temperature gradient within the device. This drives the directional diffusion of charge carriers and generates a potential difference, achieving photoelectric signal conversion.

[0004] Compared to traditional photodetectors that only detect light intensity and wavelength, polarization-sensitive detectors can acquire information about the polarization dimension of light, providing new degrees of freedom for photoelectric information encoding, transmission, and detection. This offers irreplaceable value in fields such as remote sensing mapping, precision navigation, astronomical observation, and military detection. The core of polarization detection lies in the significant in-plane anisotropy of the active layer material. Current mainstream solutions mostly rely on external geometric structure manipulation to achieve anisotropy; however, this method requires complex patterning and alignment processes, significantly increasing fabrication difficulty and hindering the miniaturization, arraying, and integration of devices.

[0005] In recent years, in-plane anisotropic two-dimensional materials have provided new directions for improving the performance and simplifying the fabrication of polarization detectors. These materials are composed of parallel or antiparallel stacked one-dimensional twisted chain structures. Their low symmetry endows them with unique anisotropic electrical, photoelectric, and thermal properties, enabling efficient polarization detection without complex micro-nano fabrication, thus becoming a core research area for next-generation polarization detectors. However, currently reported two-dimensional anisotropic materials generally suffer from limited bandgap ranges and low photoelectric conversion efficiencies, severely limiting their application in polarization detection in the visible light band and failing to meet the practical requirements of high-precision, wide-band detection. Therefore, there is an urgent need to develop novel two-dimensional anisotropic materials and device structures that combine broadband response and high sensitivity to overcome existing technological bottlenecks.

[0006] To address the aforementioned bottlenecks, there is an urgent need to explore novel two-dimensional material systems that combine broad-spectrum response, high anisotropy, and excellent optoelectronic properties. Summary of the Invention

[0007] To address the problems existing in the prior art, this invention provides a method based on two-dimensional AgNb2PS. 10 Fabrication of a broadband polarization optical detector using materials. This invention employs a novel two-dimensional layered material, AgNb2PS. 10 As the core active functional layer of a polarization photodetector, this material naturally possesses strong in-plane anisotropy, a bandgap structure suitable for wide-band detection, and excellent photoelectric conversion capabilities. It can achieve high-sensitivity polarization detection without complex patterning and alignment processes.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing a two-dimensional layered transition metal chalcogenide compound, comprising the following steps: Using chemical vapor transport (CVT) with elemental silver, niobium, phosphorus, and sulfur as raw materials and elemental iodine as the growth transport agent, the raw materials and transport agent were loaded into a quartz tube. The quartz tube was then evacuated and sealed, and placed in a dual-temperature zone tube furnace. The reaction section was heated to T1, and the growth section was heated to T2. The temperature was maintained for a period of time, then heating was stopped and the tube was allowed to cool naturally to room temperature. Large-sized, high-quality two-dimensional layered transition metal chalcogenide AgNb2PS was grown inside the quartz tube. 10 .

[0009] Furthermore, T1 is 850-950 ℃, and the heating rate is 2-5 ℃ / min; T2 is 900-1100 ℃, and the heating rate is 2-5 ℃ / min; the heat preservation period refers to heat preservation for 3-4 weeks.

[0010] Furthermore, the molar ratio of the silver, niobium, phosphorus and sulfur elements is approximately 1:2:1:10, and the total mass of the silver, niobium, phosphorus and sulfur elements is 0.5-0.7 g.

[0011] Furthermore, the total amount of elemental silver, elemental niobium, elemental phosphorus, and elemental sulfur, and the mass ratio of the amount of transport agent used, are 10:0.9-1.1.

[0012] A second aspect of the present invention provides a two-dimensional layered transition metal chalcogenide prepared by the above-described preparation method, wherein the longitudinal dimension of the two-dimensional layered transition metal chalcogenide exceeds 10 mm.

[0013] A third aspect of the present invention provides an application of the above-mentioned two-dimensional layered transition metal chalcogenide compound, wherein the application is to prepare two-dimensional material light-emitting devices or photodetectors.

[0014] A fourth aspect of the present invention provides a method for preparing a polarization broadband response photodetector using the above-described two-dimensional layered transition metal chalcogenide compound, comprising the following steps: The two-dimensional layered transition metal chalcogenide compound was exfoliated by mechanical exfoliation to obtain a few-layer two-dimensional material. Then, the few-layer two-dimensional material was transferred onto a silicon wafer by dry transfer. Conductive metal electrodes were fabricated on the surface of the few-layer two-dimensional material by photolithography and electron beam evaporation.

[0015] Furthermore, the mechanical peeling process uses Scotch tape, and the dry transfer process uses PDMS.

[0016] Furthermore, the thickness of the few-layer two-dimensional material is less than 100 nm, and the surface of the silicon wafer is SiO2 with a thickness of 285-325 nm.

[0017] The fifth aspect of the present invention provides a polarization broadband response photodetector prepared by the above-described method.

[0018] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention discloses a class of two-dimensional layered transition metal chalcogenides, and provides their synthesis process and practical application scheme. Using Ag, Nb, P, and S as basic reactants, and elemental I2 as a gas-phase transport agent, a large-size, high-crystallinity two-dimensional transition metal chalcogenide AgNb2PS was synthesized for the first time using a chemical vapor transport process. 10 Mechanical exfoliation of the product yields a few-layer sheet, which possesses excellent photoelectric properties and can be applied to light-emitting elements and photoelectric detection devices. This also marks the first application of the two-dimensional transition metal chalcogenide AgNb2PS. 10 It is used in polarization broadband response photodetectors.

[0019] (2) AgNb2PS prepared by the present invention 10 The material not only exhibits excellent photoelectric response characteristics but also boasts high photoelectric conversion efficiency. Compared to existing mainstream two-dimensional anisotropic materials, it significantly improves the photothermal conversion and photoelectric signal output capabilities of devices, thereby enhancing polarization detection sensitivity and signal-to-noise ratio. This addresses issues such as the conversion efficiency and detection accuracy of current materials, resulting in a substantial improvement in the core detection performance of the device.

[0020] (3) The raw materials of this invention are low in cost, the experimental steps are simple, and the production process is environmentally friendly; the resulting materials have good application and development potential in luminescent and photoelectric detection equipment. Attached Figure Description

[0021] Figure 1 AgNb2PS prepared in Example 1 10 Optical photograph of a large single crystal.

[0022] Figure 2 AgNb2PS prepared in Example 1 10 XRD scanning electron microscope image of the crystal.

[0023] Figure 3 AgNb2PS prepared in Example 1 10 EDS energy spectrum of the crystal.

[0024] Figure 4 AgNb2PS prepared in Example 1 10 Crystals 50-200cm -1 Raman diffraction intensity peak diagram.

[0025] Figure 5 AgNb2PS prepared in Example 1 10 Crystals 50-200cm -1 Raman diffraction intensity peak variation with angle peak intensity.

[0026] Figure 6 AgNb2PS prepared in Example 2 10 Polarization broadband response photodetector device.

[0027] Figure 7 AgNb2PS prepared in Example 2 10 Photoresponse diagram of a polarization broadband response photodetector at 671 nm.

[0028] Figure 8 AgNb2PS prepared in Example 2 10 Photoelectric response diagram of polarized light at 532 nm for a polarization broadband response photodetector.

[0029] Figure 9 AgNb2PS prepared in Example 2 10 Photoelectric response diagram of polarized light at 671 nm for a polarization broadband response photodetector. Detailed Implementation

[0030] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0032] Example 1: Two-dimensional layered transition metal chalcogenide AgNb2PS 10 Preparation, characterization and testing Weigh Ag, Nb, P, and S powders and transport agent I2 and load them into a quartz tube. The molar ratio of Ag:Nb:P:S is 1:2:1:10. The total mass of Ag, Nb, P, and S powders is 0.5 g, and the mass of transport agent I2 is 0.05 g. Evacuate the tube to 1×10⁻⁶. -3 Pa was applied and the quartz tube was sealed. The sealed quartz tube was then placed in a dual-temperature zone tube furnace. The reaction section was heated to 900 °C at a rate of 2 °C / min, and the growth section was heated to 1000 °C at a rate of 2 °C / min. The temperature was maintained for 3 weeks. After the reaction time was completed, heating was stopped, and the tube was allowed to cool naturally to room temperature. Large-sized, high-quality two-dimensional layered transition metal chalcogenide AgNb2PS was grown inside the quartz tube. 10 Large single crystals, their optical photographs are as follows Figure 1 As shown, the lateral dimension exceeds 5 mm. AgNb2PS 10 XRD scanning electron microscope image of the crystal is shown below Figure 2 As shown, the red curve below represents AgNb2PS. 10 The standard spectrum of the powder is shown above. The black curve represents the spectrum obtained from the experimental test in this embodiment. As can be seen from the figure, the two have a high degree of overlap, indicating that it is a relatively pure AgNb2PS. 10 Crystal. AgNb2PS 10 The EDS spectrum of the crystal is as follows Figure 3 As shown in the spectrum, AgNb2PS 10 Successfully prepared, with an atomic ratio of approximately 1:2:1:10 for Ag:Nb:P:S. AgNb2PS 10 Crystals 50-200cm-1 Raman diffraction intensity peak diagram as shown Figure 4 As shown in the figure, the Raman spectrum reveals that AgNb2PS 10 Good crystallinity. AgNb2PS 10 Crystals 50-200cm -1 The graph shows the variation of Raman diffraction intensity peaks with angle peak intensity. Figure 5 As shown, it can be seen that AgNb2PS 10 Raman peaks exhibit strong in-plane anisotropy depending on the angle of laser irradiation.

[0033] Example 2: AgNb2PS 10 Fabrication and Testing of Polarization Broadband Response Photodetectors The two-dimensional layered transition metal chalcogenide AgNb2PS prepared in Example 1 was treated with Scotch tape. 10 Mechanical exfoliation was performed to obtain a few-layer two-dimensional material with a thickness of less than 100 nm. The exfoliated few-layer two-dimensional material was then transferred to the surface of a silicon wafer (the surface layer of the silicon wafer is silicon dioxide, and the thickness of silicon dioxide (SiO2) is 285 nm) using PDMS. A layer of positive adhesive was spin-coated on the surface of the silicon wafer and heated at 100 °C for 4 minutes on a heating stage to fix and stabilize the positive adhesive.

[0034] By exposing the silicon wafer to ultraviolet light using a photolithography machine, the specific electrode pattern area is modified with positive photoresist. The silicon wafer is then placed in a tetramethylammonium hydroxide solution as a developer for 15 seconds. After development, the wafer is removed, and the blank area of ​​the specific electrode pattern is obtained.

[0035] 10 nm of Ti and 70 nm of Au were deposited on the surface of a silicon wafer using electron beam evaporation.

[0036] After the evaporation process is completed, the silicon wafer with the deposited metal film is immersed in acetone solvent. Taking advantage of the selective dissolution properties of acetone solvent, the unexposed positive photoresist on the surface of the silicon wafer is etched away. At the same time, the metal film remaining on the surface of the photoresist layer is peeled off, and the functional material layer of the preset pattern structure and the metal electrode structure that is closely attached to it are precisely preserved, thus completing the initial preparation of the substrate of the target optoelectronic device.

[0037] Further refined pattern removal processing was performed on the device substrate: The gold-plated silicon wafer prepared by photolithography and vapor deposition was placed in a petri dish containing acetone solution and immersed at a constant temperature for 15–30 minutes. The sol-gel release effect of acetone was fully utilized to allow the metal layer in the non-patterned areas of the silicon wafer to detach from the silicon substrate. After immersion, an airflow method using a dropper was used to thoroughly remove excess gold layer from the device surface, except for the pre-set electrode areas, precisely exposing the complete electrode pattern structure. The processed silicon wafer was then transferred to deionized water for cleaning to remove residual solvent and metal debris. Finally, the silicon wafer surface was dried with high-purity nitrogen gas, resulting in a structurally complete and precisely patterned polarization-band-response optoelectronic device under test, such as… Figure 6 As shown.

[0038] After device fabrication, device packaging, docking, and optoelectronic performance testing were performed. Using wire bonding, fine copper wires were used to connect the metal electrodes of the optoelectronic device to the circular IC socket of the test platform. The fabricated polarization broadband response detector was then fixedly mounted on the test base and docked. A complete optoelectronic testing system was built using alligator clips and a digital source meter. The device's current-voltage (IV) characteristic curve was tested using the built-in test program of the digital source meter. 532nm and 671nm lasers were used as incident light sources, and the corresponding wavelengths of laser light were sequentially and perpendicularly irradiated onto the photosensitive area of ​​the polarization broadband response detector. Simultaneously, the corresponding optoelectronic response data were collected and recorded by the digital source meter, completing the systematic testing of the device's optoelectronic performance. AgNb2PS 10 The photoresponse diagram of the polarization broadband response photodetector at 671 nm is shown below. Figure 7 As shown, the test results demonstrate that the device possesses significant photoelectric response characteristics, with the response signal intensity increasing synchronously with the increase of illumination power. Photoelectric characterization results confirm that the two-dimensional transition metal chalcogenide AgNb2PS... 10 It exhibits superior photoelectric response. AgNb2PS 10 The polarization photoelectric response diagram of the polarization broadband response photodetector at 532 nm is shown below. Figure 8 As shown, AgNb2PS 10 The photoelectric response diagram of the polarized light at 671 nm of the polarization broadband response photodetector is shown below. Figure 9 As shown, the response exhibits a periodic variation with different polarization angles, demonstrating a higher polarization ratio compared to most single-material optoelectronic devices. These results prove that AgNb2PS... 10 The detector enables polarization-sensitive broadband light detection and exhibits a relatively high dichroic ratio of 2.40. The prepared AgNb2PS... 10The photoelectric response of the photodetector device under 671 nm and 532 nm laser excitation was studied. The test results show that the device exhibits significant photoelectric response characteristics, with the response signal intensity increasing synchronously with increasing illumination power. Both the positive and negative electrodes of this polarization broadband response detector can excite a photocurrent signal that continuously varies with the polarization angle. The angle dependence curve of the photocurrent exhibits a typical sinusoidal variation with good fitting effect. Characterization results confirm the two-dimensional transition metal chalcogenide AgNb₂PS 10 It has excellent photoelectric response performance and can be used to construct multifunctional photoelectric detection elements with high sensitivity and fast response speed, providing new technical solutions for the photoelectric detection industry.

[0039] In summary, based on AgNb2PS 10 Nanosheet detectors combine anisotropic light absorption and thermoelectric properties, possessing excellent device structure and showing great potential for broadband, polarization-sensitive, room-temperature, and highly responsive self-powered optical detection.

[0040] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A method for preparing a two-dimensional layered transition metal chalcogenide, characterized in that, Includes the following steps: Using chemical vapor transport (CVT) with elemental silver, niobium, phosphorus, and sulfur as raw materials and elemental iodine as the growth transport agent, the raw materials and transport agent were loaded into a quartz tube, which was then evacuated and sealed. The tube was then placed in a dual-temperature zone tube furnace. The reaction section was heated to T1, and the growth section to T2. The temperatures were maintained for a period of time, then heating was stopped and the furnace was allowed to cool naturally to room temperature, yielding a two-dimensional layered transition metal chalcogenide, AgNb₂PS. 10 .

2. The method for preparing a two-dimensional layered transition metal chalcogenide material according to claim 1, characterized in that, The temperature range T1 is 850-950 ℃, with a heating rate of 2-5 ℃ / min; the temperature range T2 is 900-1100 ℃, with a heating rate of 2-5 ℃ / min; the holding period refers to 3-4 weeks.

3. The method for preparing a two-dimensional layered transition metal chalcogenide material according to claim 1, characterized in that, The molar ratio of the silver, niobium, phosphorus and sulfur elements is 1:2:1:10, and the total mass of the silver, niobium, phosphorus and sulfur elements is 0.5-0.7 g.

4. The method for preparing a two-dimensional layered transition metal chalcogenide material according to claim 1, characterized in that, The total amount of elemental silver, elemental niobium, elemental phosphorus, and elemental sulfur used, and the mass ratio of the amount of transport agent used, are 10:0.9-1.

1.

5. A two-dimensional layered transition metal chalcogenide prepared by the preparation method according to any one of claims 1-4, characterized in that, The longitudinal dimension of the two-dimensional layered transition metal chalcogenide exceeds 10 mm.

6. An application of the two-dimensional layered transition metal chalcogenide as described in claim 5, characterized in that, The application is to prepare two-dimensional material light-emitting devices or photodetectors.

7. A method for preparing a polarization broadband response photodetector using the two-dimensional layered transition metal chalcogenide compound as described in claim 5, characterized in that, Includes the following steps: The two-dimensional layered transition metal chalcogenide compound was exfoliated by mechanical exfoliation to obtain a few-layer two-dimensional material. Then, the few-layer two-dimensional material was transferred onto a silicon wafer by dry transfer. Conductive metal electrodes were fabricated on the surface of the few-layer two-dimensional material by photolithography and electron beam evaporation.

8. The method according to claim 7, characterized in that, The mechanical peeling method uses Scotch tape, while the dry transfer method uses PDMS.

9. The method according to claim 7, characterized in that, The thickness of the few-layer two-dimensional material is less than 100 nm, and the surface of the silicon wafer is SiO2 with a thickness of 285-325 nm.

10. A polarization broadband response photodetector prepared by the method as described in claim 7.